Characterisation and distribution of deposited trace elements transported over long and intermediate distances in north-eastern France using Sphagnum peatlands as a sentinel ecosystem. (January 2015) - Meyer, Caroline; Diaz-de-Quijano, Maria; Monna, Fabrice; Franchi, Marielle; Toussaint, Marie-Laure; Gilbert, Daniel; Bernard, Nadine
Abstract: Trace elements in the form of particulate matter can be transported downwind from their emission sources and may have negative effects on human health and ecosystems. The transport of trace elements is often studied by monitoring their accumulation in mosses. The aim of this study was to characterise and describe the distribution of deposited trace elements transported over long and intermediate distances in north-eastern France, a location far from the main emission sources. We analysed the trace element accumulation in Sphagnum capillifolium in 54 ombrotrophic peatlands distributed in six regions of France (Alps, Jura, Massif Central, Morvan, Rhône corridor and Vosges). The concentrations of Al, Cd, Cr, Cu, Fe, Pb, Ti, V, and Zn in the surface were determined in three replicate samples of Sphagnum within each peatland. The enrichment factors calculated using Ti as the element of reference clearly exhibited a predominant anthropogenic origin for Cd, Cu, Pb, and Zn, although the concentrations were relatively low compared to those found in other studies. The isolation of the peatlands from any fixed and traffic emission source suggests an intermediate and/or long-distance transport of the pollutants from their emission sources. The structure of the compositional dataset was explored using a covariance biplot. The first score was used as a synthetic indicator of the origin of the deposits and the degree of contamination of each peatland. This new index showed that the Vosges and the Alps were the regions most affected by high enrichment of trace elements, particularly Pb and Cd. The erosion of soils highly contaminated by former mining and smelting activities in the Vosges and the polluted cities and busy highways in the Alps may account for these distributions. The Jura was the least affected region sampled, and the other regions presented intermediate anthropogenic deposits. This study provides valuable information concerning the management and protection of these ecosystems. Highlights: First characterisation of long-range deposition using sphagnum peatlands in France. Cd, Zn, Pb and Cu are predominantly of anthropogenic origin. A new synthetic indicator describes the deposition of anthropogenic elements. Vosges and Alps are the most affected by anthropogenic deposition.